Risk Assessment and Management of Venous Thromboembolism in Women during Pregnancy and Puerperium (SAVE): An International, Cross-sectional Study - Gris, Jean-Christophe; Aoun, Joseph; Rzaguliyeva, Leyla; Begum, Rowshan; Salah, Hassan; Tugushi, Tatia; Ghani-Chabouk, Mohammed; Zibdeh, Mazen; Jassar, Waleed Al; Abboud, Joe; Meziane, Nadia; Ajayi, Godwin-Olufemi; Hossain, Nazli; Pyregov, Alexey; Abduljabbar, Hassan; Snyman, Leon C.; Rachdi, Radhouane; Tahlak, Muna-Abdulrazzaq; Najmutdinova, Dilbar; the SAVE Study Group (TH Open, 2018)
The clinical burden of obstetric venous thromboembolism (VTE) risk is inadequately established. This study assessed the prevalence and management of VTE risk during pregnancy and postpartum outside the Western world. This international, noninterventional study enrolled adult women with objectively confirmed pregnancy attending prenatal care/obstetric centers across 18 countries in Africa, Eurasia, Middle-East, and South Asia. Evaluations included proportions of at-risk women, prophylaxis as per international guidelines, prophylaxis type, factors determining prophylaxis, and physicians' awareness about VTE risk management guidelines and its impact on treatment decision. Data were analyzed globally and regionally. Physicians (N = 181) screened 4,978 women, and 4,010 were eligible. Of these, 51.4% were at risk (Eurasia, 90%; South Asia, 19.9%), mostly mild in intensity; >90% received prophylaxis as per the guidelines (except South Asia, 77%). Women in Eurasia and South Asia received both pharmacological and mechanical prophylaxes (>55%), while pharmacological prophylaxis (>50%) predominated in Africa and the Middle-East. Low-molecular-weight heparin was the pharmacological agent of choice. Prophylaxis decision was influenced by ethnicity, assisted reproductive techniques, caesarean section, and persistent moderate/high titer of anticardiolipin antibodies, though variable across regions. Prophylaxis decision in at-risk women was similar, irrespective of physicians' awareness of guidelines (except South Asia). A majority (>80%) of the physicians claimed to follow the guidelines. More than 50% of women during pregnancy and postpartum were at risk of VTE, and >90% received prophylaxis as per the guidelines. Physicians are generally aware of VTE risk and comply with guidelines while prescribing prophylaxis, although regional variations necessitate efforts to improve implementation of the guidelines.
Keywords: pregnancy; prophylaxis; puerperium; risk assessment and management; venous thromboembolism